Pengelolaan Bidang Sarana dan Prasarana dalam Meningkatkan Kompetensi Peserta Didik - Ibrohim, Maulana Malik; Mahmudah, Fitri Nur (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research discusses the management of educational facilities and infrastructure in improving the competence of students. The purpose of this study is to describe the management of infrastructure facilities starting from planning, procurement, maintenance, elimination, and supervision. The research method used is descriptive qualitative method. The data sources of this study are principals, TU principals, teachers, and students. Data collection was carried out through observation and direct interviews with subjects. Data analysis uses qualitative data analysis techniques consisting of data reduction, data presentation, and conclusions. The results showed that the management of educational facilities and infrastructure in improving the competence of students has gone quite well. The empowerment of educational facilities and infrastructure in the SMK Muhammadiyah 3 Weleri school has been carried out well, starting from the empowerment of educational resources, both human resources, financial resources, educational institutions, and other facilities and facilities. Supervision carried out at SMK Muhammadiyah 3 Weleri school is well managed, starting from the classroom, teacher's room, tables, chairs, and all equipment that supports learning is managed as well as possible so that when the learning process begins it can run smoothly and safely without any obstacles